Captura de CO2 em peças de concreto para pavimentação através da cura por carbonatação acelerada - Benittez, Lívia Regueira Fortunato (Universidade Federal de São Carlos, 2019)
The construction sector stands out as responsible for the emission by third of the total greenhouse gases emitted by mankind. The processes of extraction and manufacture of the raw materials, necessary to obtain the concrete, emit large amounts of CO2 to the environment. However, several researches have shown that Portland cement based materials have the capacity to permanently store CO2 in the cement matrix in the form of stable calcium carbonate (CaCO3), through accelerated carbonation curing. In the carbonation reaction the carbon dioxide (CO2) reacts mainly with the calcium hydroxide (Ca(OH)2) and the hydrated calcium silicates (C - S - H), generating CaCO3, which precipitates mineralogically as calcite, vaterita and aragonite. The literature shows that the precipitation of CaCO3 in the pores of the cementitious material alters the porosity, increases the density and promotes the improvement of the physical and mechanical properties of the material, besides contributing to the environment by definitively incorporating CO2. This technology has been applied in non-reinforced steel components, such as concrete structural and non-structural masonry blocks, tiles, boards, among others; with a lack of studies related to the concrete units for pavement. Aforesaid, the present research aimed to verify, to analyze and to measure the capture of carbon dioxide (CO2) in concrete units for pavement after the accelerated carbonation curing process; to verify the applicability of the experimental procedure related to the Mass Gain Method used to obtain the value of CO2 absorption; if there was an improvement in the physical and mechanical properties of carbonated concrete units for pavement (PCPs) regarding those one made up by conventional process. To do this, some specimens, produced in an industrial scale, were preliminarily submitted to 12 hours of initial steam cure and 12 hours without initial steam cure, followed by accelerated carbonatation curing for 4 and 16 hours, this occurred in a carbonation chamber set up with 20 % CO2 concentration, 23°C and 65% relative humidity. subsequently, the absorption of CO2 was measured by the Mass Gain Method and checked out by sprinkling the acid-base indicator phenolphthalein; and the mechanical properties were measured at 02 and 28 days, by compressive tests, abrasion resistance test and water absorption test. The results indicated that the Mass Gain Method is feasible to obtain the percentage of the CO2 absorption; all the samples submitted to accelerated carbonation treatment captured CO2, the highest absorption found was 5.1% for the PCPs submitted to 12 hours without initial steam cure with a subsequent 16 hours of carbonation; in addition, the compressive strength gain in the carbonated samples was verified, and at the 02 days this presented better resistance to the axial compression of 40.7 MPa, to the detriment of the reference PCPs (non-carbonated) that presented 37,2 MPa; and at 28 days the best results were again verified for the carbonated PCPs (46.4MPa) in detriment to the reference PCPs (40.7MPa); as for abrasion resistance and water absorption, the carbonated and reference PCPs did not present a significant difference. Therefore, it was concluded that the accelerated carbonation cure procedure in addition to the environmental improvement regarding the CO2 capture, promotes the speed up of the PCP manufacturing, since the carbonated samples presented high compressive strength at early ages.
CO2 capture in concrete units for pavement through accelerated carbonation cure
Keywords: Carbonatação acelerada; Cura; Absorção de CO2; Peças de concreto para pavimentação; Resistência; Concreto; CO2 absorption; Accelerated carbonation; Concrete units for pavement; Curing; Strength; Concrete; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS